Marginalizing Extremism among Middle-class Citizens in Malaysia (International Journal of Psychosocial Rehabilitation, 2020)
Islam has been labeled as a religion advocating violence by the non-Muslim global community due to the terrorist attacks at the World Trade Center (WTC) in the USA. Since then, the term 'extremism' has become popular, and more synonyms attribute all negative things to the Muslim community, thus producing the term 'Islamophobia.' In Malaysia, this term also becomes a hot issue discussed by researchers in sociology and Islamic studies. Understanding extremism is still superficial among Malaysians. There are not many popular or scientific writings that explain the meaning of extremism in a concrete and easy-to-understand manner. Based on the literature review, the definition of extremism is further characterized by Western figures. Notwithstanding that there are some writings from local scholars, they are not comprehensive and mostly focus only on certain minor aspects. There are three main objectives in this study. Firstly, this research is conducted to understand the concept of extremism in general based on other studies of politics, psychology, and Islamic views. The second objective is to identify the root cause of the emergence of extremism. Lastly, this study aims to find out the circumstances or forms of extremism that existed in Malaysia. This study is qualitative, using an inductive analytical method. Data were collected from various sources of related documents, such as books, newspapers, reports, articles, official documents, and so on. The study has found that at least one important element that creates extremism is 'self-threat.' This element can be balanced with economic development, a middle class, political stability, democracy, and using dialogue as a solution.